Comparison of anti-mullerian hormone and antral follicle count for assessment of ovarian reserve - Sonal Panchal; Chaitanya Nagori (Wolters Kluwer Medknow Publications, 2012)
Aim: This study aims to compare the efficacy of AFC and AMH, as markers for ovarian reserve. Materials and Methods: 75 patients with PCO (polycystic ovaries) undergoing IVF were randomized with 75 non-PCO patients. On day 3, volume of ovary was acquired, ovarian volume was defined by VOCAL, and Sono AVC was used to count the number of antral follicles. Sum total of antral follicles in both ovaries was taken as total antral follicle count (AFC). AMH was measured on the same day. Long agonist protocol with recombinant FSH (rFSH) was used for IVF stimulation till at least two follicles of 18 mm were seen. hCG 10,000 iu was given and ovum pick up was done after 34-35 h. Primary end point was number of follicles >12 mm seen on day of hCG. Final end point was number of ova retrieved on ovum pick up. Correlation of AFC and AMH was checked for both end points and with each other. Results: Correlation of AFC and follicles >12 mm on day of hCG in PCO group is 0.56 and non-PCO group is 0.63, 1 and for AMH and follicles >12 mm on day of hCG in PCO group is 0.42 and non-PCO group is 0.47. Correlation of AFC with number of ova retrieved on OPU in PCO group is 0.44 and for non-PCO group is 0.50. The value for AMH is 0.39 in PCO and 0.43 for non-PCO group. Comparing correlation of AFC and AMH for primary end point in PCO group has 'z' value 1.11(onetailed significance 0.1335, twotailed significance 0.267) and in non-PCO group comparison shows a 'z' value of 1.39 (one tailed significance 0.0823, two-tailed significance 0.1645). Therefore in both groups, AFC and AMH correlates with total number of follicles >12 mm on day of hCG, but both AFC and AMH have independent significance. Comparing correlation of AFC and AMH with number of ova retrieved on OPU, in non-PCO group has 'z' value of 0.54(one tailed 0.2946, two-tailed 0. 5892). In PCO group, this comparison shows, 'z' value of 0.36(one tailed 0.3594, two tailed 0.7188). Conclusion: AFC and AMH correlate with each other but have independent significance for estimating follicles >12 mm on day of hCG. For ova retrieved on OPU, in PCO group, AMH and AFC have similar significance. In non-PCO, AMH may increase accuracy of estimation of number of ova retrieved on OPU over AFC, but difference is not significant. AFC only may suffice for estimation of number of ova retrieved on OPU for all practical purposes.